Harvesting the Benefits of Precision Agriculture in an Uruguayan Rice Crop - Bonilla, Camila; Terra, José A.; Gutiérrez, Lucía; Roel, Álvaro (Agrociencia Uruguay, 2015)
The objective of this study was to develop a methodology for processing information from a rice field generated by yield monitors; and its subsequent use as a starting point to a site-specific management. The spatiotemporal variability of the yield monitor data relayed for two years in a commercial rice field of 100 ha was quantified and characterized. The effect of agronomy management factors and the spatial distribution of soil properties as the causes of the yield spatial variability were explored. Besides, an economic analysis with maps of net income was performed. The cluster analysis identified two zones of contrasting yield. Associated with them, differences in sand content, soil phosphorus, plant emergence, water depth, and weed control were found. The economic analysis showed that the low-yield zone presented average losses of 361 American dollars ha-1 and the high yield zone had average earnings of 280 dollars ha-1. Our study demonstrates that the technologies associated with precision agriculture allow the analysis of the yield spatial variability in fields that a first glance seem uniform. Two yield zones, which potentially could benefit from site-specific management, were identified. The simple data transformation of the yield data on a map of net income constitutes a very useful tool to make decisions about the potential strategies of site-specific management on this farm.